DEONTIC MODALITY AND MODALS IN THE LANGUAGE OF CONTRACTS - MATULEWSKA, Aleksandra (Comparative Legilinguistics, 2017)
The purpose of this paper is to present most typical methods of expressing deontic modality, namely obligation, prohibition and permission in Polish, American and British contracts. The author has analyzed the corpora of about 45 contracts formulated in British-English, American-English and Polish, namely: (i) deeds of conveyance, (ii) contracts of sale, (iii) contracts of lease, (iv) logistic contracts, (v) deeds of partnership and company-related contracts, (vi) contracts for rendering services and (vii) contracts of employment. After presenting the exponents of deontic modality, the author compiles the results in tables to show potential translative equivalents. The listing of such exponents of modality may serve translation purposes in accordance with textual-normative equivalence (cf. Kierzkowska 2002).